A novel fast-response positive electrode material and a preparation method thereof, and a thermal battery
Patent Information
- Application Number
- CN202311350577.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-18
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2043-10-18
AI Technical Summary
[0005]本发明旨在提供一种新型快响应正极材料及其制备方法、热电池,有效解决现有热电池激活时间长、带载能力弱的问题
[0017]本发明采用的另一技术方案是:一种热电池,其包含如上任一所述新型快响应正极材料或采用如上任一所述的制备方法制得的新型快响应正极材料。
Smart Images

Figure CN117497692B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of thermal battery technology, and in particular to a novel fast-response cathode material and its preparation method, as well as a thermal battery. Background Technology
[0002] A thermally activated battery, also known as a thermally activated reserve battery, is a primary battery that uses its own heating system to heat a non-conductive solid salt electrolyte at room temperature to a molten ionic state to operate. Due to its many advantages, such as short activation time, high power density, long storage time, and wide operating temperature range, it is widely used in weapon systems such as torpedoes and missiles.
[0003] As a power source for defense equipment, the technological development of thermal batteries directly impacts the combat performance of weapon systems. To meet the electrical energy demands of weapon systems targeting different objectives in modern warfare, the performance requirements for thermal batteries, such as activation time and load-carrying capacity, are becoming increasingly stringent. The main factors affecting the activation time of thermal batteries include the burning rate of the propellant and the heat transfer rate within the stack, while the load-carrying capacity is primarily related to the electrical conductivity of the electrode materials. Currently, conventional thermal battery cathode materials such as FeS2, CoS2, and NiS2 are limited by their material properties, resulting in low electrical and thermal conductivity, which is gradually failing to meet the requirements of new weapon systems. Therefore, developing novel fast-response cathode materials that combine rapid activation and high load-carrying capacity to further improve thermal battery technology is a crucial direction for current thermal battery development.
[0004] Metal borides (MB2, M = Al, Ti, Zr, Hf, etc.), as ceramic materials, are hexagonal crystal compounds with a two-dimensional network structure. They possess both extremely high electrical and thermal conductivity, and also exhibit excellent heat resistance. Currently, they are widely used in many fields such as conductive ceramics, nanoelectronic devices, electrochemical energy storage, and metal smelting. Metal boride ceramic materials, with their high electrical and thermal conductivity, can be used as conductive and thermally conductive additives to accelerate the heat transfer rate of the positive electrode material in the initial activation stage of thermal batteries, shorten the activation time, and reduce the internal resistance during the operation of the thermal battery, thereby comprehensively improving the electrochemical performance of the thermal battery. Summary of the Invention
[0005] The present invention aims to provide a novel fast-response cathode material and its preparation method, as well as a thermal battery, which effectively solves the problems of long activation time and weak load-carrying capacity of existing thermal batteries.
[0006] To solve the above-mentioned technical problems, one technical solution adopted by the present invention is: a novel fast-response cathode material, wherein, by mass fraction, the fast-response cathode material is composed of the following: 65-80 parts of cathode active material, 0.5-4 parts of lithiation agent, 15-30 parts of eutectic salt electrolyte and 1-5 parts of conductive and thermally conductive additive, wherein the conductive and thermally conductive additive is a metal boride with a two-dimensional network structure.
[0007] In some feasible embodiments, the conductive and thermally conductive additive includes one or more of AlB2, TiB2, ZrB2, and HfB2.
[0008] In some feasible embodiments, the conductive and thermally conductive additive has a particle size of 500 nm to 100 μm and a specific surface area of 1 to 50 m². 2 / g.
[0009] In some feasible embodiments, the positive electrode active material includes one or more of FeS2, CoS2, NiS2, NiCl2, NiF2, and MnO2.
[0010] In some feasible embodiments, the particle size of the positive electrode active material is 10 μm to 50 μm.
[0011] In some feasible embodiments, the lithiating agent is Li₂O, and the eutectic salt electrolyte is one of LiCl-KCl, LF-LiCl-LiBr, LiF-LiBr-KBr, and LiCl-LiBr-KBr.
[0012] Another technical solution adopted in this invention is: a method for preparing a novel fast-response cathode material as described above, the steps of which include: mixing the cathode active material with a conductive and thermally conductive additive, adding a lithiation agent and a eutectic salt electrolyte, and then sintering at high temperature, cooling, crushing and sieving to obtain the novel fast-response cathode material.
[0013] In some feasible embodiments, the conductive and thermally conductive additive is crushed and sieved before the positive electrode active material is mixed with the conductive and thermally conductive additive, with a sieve size of 80 to 200 mesh.
[0014] The positive electrode active material and the conductive and thermally conductive additive are mixed using a ball mill at a speed of 400 r / min to 600 r / min for 1 h to 3 h.
[0015] In some feasible embodiments, high-temperature sintering is performed by constant heating at 250–450°C for 2–4 hours in an inert gas environment;
[0016] During cooling, the cooling rate is 5℃ / min to 10℃ / min.
[0017] Another technical solution adopted in this invention is: a thermal battery comprising any of the novel fast-response cathode materials described above or a novel fast-response cathode material prepared by any of the preparation methods described above.
[0018] The beneficial effects of this invention are as follows: Using metal borides as conductive and thermally conductive additives to prepare novel fast-response cathode materials can accelerate the heat transfer rate of the cathode material in the initial activation stage, shorten the activation time of the thermal battery, and simultaneously enhance the conductivity of the cathode material, thereby reducing the internal resistance during thermal battery operation and improving the battery's load-carrying capacity. Furthermore, metal borides possess excellent heat resistance properties, effectively resisting significant thermal shock to the surface of the cathode material, thus comprehensively improving the electrochemical performance of the thermal battery. Attached Figure Description
[0019] Figure 1 A comparison chart of activation times of thermal batteries made using the fast-response cathode material prepared in Example 1 of the present invention and the cathode material prepared in Comparative Example 1.
[0020] Figure 2 This is a comparison chart of the internal resistance of thermal batteries made using the fast-response cathode material prepared in Example 1 of the present invention and the cathode material prepared in Comparative Example 1. Detailed Implementation
[0021] The technical solutions of the embodiments of the present invention will be described in detail below with reference to the accompanying drawings.
[0022] This invention relates to a novel fast-response cathode material and its preparation method, as well as a thermal battery. The novel fast-response cathode material is prepared using metal borides as conductive and thermally conductive additives, which accelerates the heat transfer rate of the cathode material in the initial activation stage, shortens the activation time of the thermal battery, and simultaneously enhances the conductivity of the cathode material, reduces the internal resistance during thermal battery operation, and improves the load-carrying capacity of the thermal battery. Furthermore, metal borides possess excellent heat resistance properties and can effectively withstand significant thermal shock to the surface of the cathode material, thereby comprehensively improving the electrochemical performance of the thermal battery.
[0023] In this invention, the fast-response cathode material is composed of the following components by mass fraction: 65-80 parts of cathode active material, 0.5-4 parts of lithiation agent, 15-30 parts of eutectic salt electrolyte, and 1-5 parts of conductive and thermally conductive additive, wherein the conductive and thermally conductive additive is a metal boride with a two-dimensional network structure.
[0024] The aforementioned positive electrode active materials include one or more of FeS2, CoS2, NiS2, NiCl2, NiF2 and MnO2, with a particle size of 10μm to 50μm.
[0025] The lithium-ionizing agent mentioned above is Li2O.
[0026] The aforementioned eutectic salt electrolyte is one of LiCl-KCl, LF-LiCl-LiBr, LiF-LiBr-KBr, and LiCl-LiBr-KBr.
[0027] The aforementioned conductive and thermally conductive additives were prepared using a self-propagating high-temperature synthesis method, achieving a purity greater than 97%. These additives include one or more of AlB2, TiB2, ZrB2, and HfB2. The particle size of both single metal borides and mixtures of multiple metal borides should be 500 nm to 100 μm, with a specific surface area of 1 to 50 m². 2 / g.
[0028] The method for preparing the above-mentioned novel fast-response cathode material includes the following steps:
[0029] The conductive and thermally conductive additives are crushed and sieved, with a screen size of 80-200 mesh.
[0030] The positive electrode active material and the conductive and thermally conductive additives were weighed according to the ratio and mixed by ball milling in a planetary ball mill at a speed of 400 r / min to 600 r / min for 1 h to 3 h.
[0031] A novel fast-response cathode material is obtained by adding a lithiating agent and a eutectic salt electrolyte to a well-mixed positive electrode active material and conductive and thermally conductive additives, followed by high-temperature sintering, cooling, crushing and sieving.
[0032] Preferably, the high-temperature sintering is carried out in an inert gas environment at a constant temperature of 250-450℃ for 2-4 hours; during cooling, the cooling rate is 5℃ / min-10℃ / min.
[0033] The aforementioned novel fast-response cathode material was used to prepare a thermal battery for testing. In some feasible schemes, the electrical performance testing method for the thermal battery prototype is as follows: at 2T / cm... 2 Under pressure, novel fast-response cathode materials and ternary lithium salt electrolyte powders (such as LiF-LiCl-LiBr) are pressed into monolayer sheets, and then stacked sequentially in the order of cathode sheet, electrolyte sheet, negative electrode, and current collector to form a single cell. Fifteen groups of single cells are connected in series, positive and negative, and then pressurized and sealed into a battery casing to assemble a thermal battery prototype. The assembled thermal battery prototype is then subjected to discharge testing under a 7.5A constant current superimposed with a 35A pulse load.
[0034] The present invention will now be described with reference to the accompanying drawings. Experimental methods not specifically described in terms of operation steps are performed in accordance with the corresponding product manuals. Unless otherwise specified, the instruments, reagents, and consumables used in the embodiments can be purchased from commercial companies.
[0035] Example 1:
[0036] TiB2 was ground and crushed and passed through an 80-mesh sieve. FeS2 and TiB2 were weighed at a mass ratio of 79:1, premixed, and then ball-milled at 400 r / min for 2 h using a planetary ball mill. FeS2, TiB2, Li2O, and LiF-LiCl-LiBr were mixed at a mass ratio of 79:1:2:18 and then sintered at a constant temperature of 400℃ for 4 h in a high-temperature atmosphere furnace filled with argon. After the constant temperature period, the mixture was cooled at a rate of 5℃ / min to 10℃ / min, then removed from the high-temperature atmosphere furnace, crushed, and sieved to obtain a novel fast-response cathode material.
[0037] Example 2:
[0038] HfB2 was ground and crushed and passed through a 100-mesh sieve. FeS2 and HfB2 were weighed at a mass ratio of 75:5, premixed, and then ball-milled at 600 r / min for 2 h using a planetary ball mill. FeS2, HfB2, Li2O, and LiF-LiCl-LiBr were mixed at a mass ratio of 75:5:2:18 and then sintered at a constant temperature of 450℃ for 2 h in a high-temperature atmosphere furnace filled with argon. After the constant temperature period, the mixture was cooled at a rate of 5℃ / min to 10℃ / min, then removed from the high-temperature atmosphere furnace, crushed, and sieved to obtain a novel fast-response cathode material.
[0039] Example 3:
[0040] ZrB2 was ground and crushed and passed through a 200-mesh sieve. CoS2 and ZrB2 were weighed at a mass ratio of 70:3, premixed, and then ball-milled at 400 r / min for 1 h using a planetary ball mill. CoS2, ZrB2, Li2O, and LiF-LiCl-LiBr were mixed at a mass ratio of 70:3:2:25 and then sintered at a constant temperature of 430℃ for 4 h in a high-temperature atmosphere furnace filled with argon. After the constant temperature period, the mixture was cooled at a rate of 5℃ / min to 10℃ / min, then removed from the high-temperature atmosphere furnace, crushed, and sieved to obtain a novel fast-response cathode material.
[0041] Example 4:
[0042] AlB2 was ground and crushed and passed through a 100-mesh sieve. NiS2 and AlB2 were weighed at a mass ratio of 73:2, premixed, and then ball-milled at 400 r / min for 1 h using a planetary ball mill. NiS2, AlB2, Li2O, and LiF-LiCl-LiBr were mixed at a mass ratio of 73:2:2:23 and then sintered at a constant temperature of 410℃ for 2 h in a high-temperature atmosphere furnace filled with argon. After the constant temperature period, the mixture was cooled at a rate of 5℃ / min to 10℃ / min, then removed from the high-temperature atmosphere furnace, crushed, and sieved to obtain a novel fast-response cathode material.
[0043] Comparative Example 1:
[0044] FeS2, Li2O and LiF-LiCl-LiBr were mixed evenly in a mass ratio of 80:2:18, and then sintered at a constant temperature of 400℃ in a high-temperature atmosphere furnace filled with argon for 4 hours. After the constant temperature was completed, the mixture was cooled at a rate of 5℃ / min to 10℃ / min, and then removed from the high-temperature atmosphere furnace, crushed and sieved to obtain the cathode material.
[0045] Comparative Example 2:
[0046] CoS2, Li2O and LiF-LiCl-LiBr were mixed evenly in a mass ratio of 73:2:25, and then sintered at a constant temperature of 430℃ in a high-temperature atmosphere furnace filled with argon for 4 hours. After the constant temperature was completed, the mixture was cooled at a rate of 5℃ / min to 10℃ / min, and then removed from the high-temperature atmosphere furnace, crushed and sieved to obtain the cathode material.
[0047] Comparative Example 3:
[0048] NiS2, Li2O and LiF-LiCl-LiBr were mixed uniformly in a mass ratio of 75:2:23, and then sintered at a constant temperature of 410℃ in a high-temperature atmosphere furnace filled with argon for 2 hours. After the constant temperature period, the mixture was cooled at a rate of 5℃ / min to 10℃ / min, and then removed from the high-temperature atmosphere furnace, crushed and sieved to obtain the cathode material.
[0049] The novel fast-response cathode materials prepared in Examples 1-4 and the cathode materials in Comparative Examples 1-3 were subjected to a temperature of 2 T / cm. 2 Under pressure, ternary lithium salt electrolyte powder (such as LiF-LiCl-LiBr) is pressed into a single layer, and then stacked sequentially in the order of positive electrode, electrolyte sheet, negative electrode, and current collector to form a single cell. Fifteen groups of single cells are connected in series, positive and negative, and then pressurized and sealed into a battery casing to assemble a thermal battery prototype. The assembled thermal battery prototype is then subjected to discharge testing under a constant current of 7.5A superimposed with a pulsed load of 35A.
[0050] Taking Example 1 and Comparative Example 1 as examples, refer to the appendix. Figure 1-2 The activation time of the thermal battery prototype assembled using the novel fast-response cathode prepared in Example 1 was reduced by 40%, and the internal resistance was reduced by 15%.
[0051] In the above discharge test, compared with Comparative Example 1, the activation time of the thermal battery prototype assembled with the novel fast-response cathode prepared in Example 2 was reduced by 26% and the internal resistance was reduced by 9%.
[0052] In the above discharge test, compared with Comparative Example 2, the activation time of the thermal battery prototype assembled with the novel fast-response cathode prepared in Example 3 was reduced by 35% and the internal resistance was reduced by 8%.
[0053] In the above discharge test, compared with Comparative Example 3, the activation time of the thermal battery prototype assembled with the novel fast-response cathode prepared in Example 4 was reduced by 31%, and the internal resistance was reduced by 10%.
[0054] It should be noted that the above content is merely an embodiment of the present invention. Any modifications and alterations made by those skilled in the art based on the main ideas and related content of the present invention should also fall within the scope of protection of the claims of the present invention. Furthermore, the technical terms and other materials involved in the present invention are only for clearly illustrating the advantages and effects of the present invention and should not be considered as limitations on the innovativeness of the present invention. The above embodiments are a partial description of the practical application effects of the present invention, and these embodiments are not intended to limit the patent scope of the present invention. All improvements and substitutions made by those skilled in the art based on the present invention fall within the scope of protection of the present invention.
Claims
1. A novel fast-response cathode material, characterized in that, The fast-response cathode material, by mass fraction, comprises the following: 65-80 parts of cathode active material, 0.5-4 parts of lithiating agent, 15-30 parts of eutectic salt electrolyte, and 1-5 parts of conductive and thermally conductive additive, wherein the conductive and thermally conductive additive is a metal boride with a two-dimensional network structure.
2. The novel fast-response cathode material according to claim 1, wherein: The conductive and thermally conductive additives include one or more of AlB2, TiB2, ZrB2, and HfB2.
3. The novel fast-response cathode material according to claim 2, wherein: The conductive and thermally conductive additive has a particle size of 500 nm to 100 μm and a specific surface area of 1 to 50 m². 2 / g.
4. A novel fast-response cathode material according to any one of claims 1-3, wherein: The positive electrode active material includes one or more of FeS2, CoS2, NiS2, NiCl2, NiF2, and MnO2.
5. A novel fast-response cathode material according to claim 4, wherein: The particle size of the positive electrode active material is 10 μm to 50 μm.
6. A novel fast-response cathode material according to any one of claims 1-3 and 5, wherein: The lithiating agent is Li₂O, and the eutectic electrolyte is one of LiCl-KCl, LiF-LiCl-LiBr, LiF-LiBr-KBr, and LiCl-LiBr-KBr.
7. A method for preparing a novel fast-response cathode material as described in any one of claims 1-6, comprising the steps of: The positive electrode active material is mixed with conductive and thermally conductive additives, and then a lithiation agent and a eutectic salt electrolyte are added. The mixture is then sintered at high temperature, cooled, crushed, and sieved to obtain the novel fast-response positive electrode material.
8. The method for preparing a novel fast-response cathode material according to claim 7, wherein: Before mixing the positive electrode active material with the conductive and thermally conductive additive, the conductive and thermally conductive additive is crushed and sieved with a screen size of 80 to 200 mesh. The positive electrode active material and the conductive and thermally conductive additive are mixed using a ball mill at a speed of 400 r / min to 600 r / min for 1 h to 3 h.
9. A method for preparing a novel fast-response cathode material according to claim 7, wherein: High-temperature sintering is carried out under an inert gas environment and heated at a constant temperature of 250–450℃ for 2–4 hours. During cooling, the cooling rate is 5℃ / min to 10℃ / min.
10. A thermal battery, characterized in that: It includes the novel fast-response cathode material as described in any one of claims 1-6 or the novel fast-response cathode material prepared by the method described in any one of claims 7-9.
Citation Information
Patent Citations
Novel composite anode material for thermal battery and preparation method thereof
CN102148352A
Cell
CN1311902A